2015
DOI: 10.1002/tkm2.1037
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic aspartate aminotransferase, a direct binding protein of kamikihito, regulates axon growth

Abstract: Aim: Alzheimer's disease (AD) is the most common cause of dementia. The aim of this study was to identify the direct binding proteins of kamikihito (KKT), a traditional Japanese Kampo medicine used as an anti-AD drug. Method: Using the drug affinity responsive target stability (DARTS) method, cytosolic aspartate aminotransferase (cAST) was identified as the direct binding protein of KKT. Primary cultured cortical neurons were treated with amyloid beta (Aβ)(25-35), and cAST expression and activity were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…59) Our study found that KKT treatment reversed Aβ-induced tau phosphorylation via protein phosphatase 2A (PP2A). 60) However, inactivation of PP2A by Aβ and activation of PP2A by KKT in neurons was not robust. This suggested that other main signaling pathways might work in KKT-mediated axon regeneration.…”
Section: Usefulness Of Darts Methods For Iden-tifying Unknown Signalingmentioning
confidence: 98%
“…59) Our study found that KKT treatment reversed Aβ-induced tau phosphorylation via protein phosphatase 2A (PP2A). 60) However, inactivation of PP2A by Aβ and activation of PP2A by KKT in neurons was not robust. This suggested that other main signaling pathways might work in KKT-mediated axon regeneration.…”
Section: Usefulness Of Darts Methods For Iden-tifying Unknown Signalingmentioning
confidence: 98%
“…We found that kamikihito also induced axonal growth in the Aβ-treated neuron culture and induced improvement in degenerated axons and memory in 5XFAD mice [ 39 , 98 ]. Using the DARTS method, cytosolic aspartate aminotransferase (cAST) was identified as the direct binding protein candidate of kamikihito [ 99 ]. Knock-down and pharmacological inhibition of cAST diminished the axonal growth activity of kamikihito.…”
Section: Recovery From Aβ-induced Axonal Degenerationmentioning
confidence: 99%